1992
DOI: 10.1111/j.1365-2796.1992.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral emphysematous pyelonephritis resolving to medical therapy

Abstract: We describe a case of bilateral emphysematous pyelonephritis, in a diabetic female, that responded to medical therapy alone. Her complete improvement is documented radiologically. Emphysematous pyelonephritis, as a cause of serious infection in diabetic patients, is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Most of the studies were published within the last 10 years, reflecting the increased awareness of EPN and the associated controversy. After reading the full reports, 16 studies were excluded for various reasons [4,5,9,[38][39][40][41][42][43][44][45][46][47][48][49][50]; eight were case reports [9,38,40,43,44,46,47,49], while five others were excluded as they were reporting on emphysematous cystitis [41,42,45,48,50], and two were excluded as they were systematic reviews [5,39]. The final excluded study, Wan et al [4] was excluded, as they reported an updated version of their data, which were included in this review [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies were published within the last 10 years, reflecting the increased awareness of EPN and the associated controversy. After reading the full reports, 16 studies were excluded for various reasons [4,5,9,[38][39][40][41][42][43][44][45][46][47][48][49][50]; eight were case reports [9,38,40,43,44,46,47,49], while five others were excluded as they were reporting on emphysematous cystitis [41,42,45,48,50], and two were excluded as they were systematic reviews [5,39]. The final excluded study, Wan et al [4] was excluded, as they reported an updated version of their data, which were included in this review [14].…”
Section: Resultsmentioning
confidence: 99%
“…The main focus of treatment is an emergency nephrectomy (EN), percutaneous drainage (PCD), or medical management (MM), with or with no stenting of the urinary tract. Some reports recommend that EN should be the mainstay of treatment and not be delayed [2,3], but others recommended a more conservative approach with PCD [6][7][8], and a purely conservative approach with MM alone has also been advocated [9][10][11], which further increases the management conundrum.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative (medical) treatment for EPN was suggested by some authors [7,10,11]. Aswathaman et al [11] reported complete success for conservative treatment in patients who had no risk factors such as thrombocytopenia, shock, altered sensorium, and haemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…This taboo was also rejected in recent years and a new treatment strategy of kidney preservation emerged [8][9][10][11]. The reasons for this change were the high mortality rates of emergency nephrectomy (17.6-40%) [5,6] and advances in image-guided procedures for drainage of the gas and infected fluids, using PCDs [9,10]. Chen et al [8], in their experience with 25 patients, suggested that percutaneous drainage is safe and effective for EPN, and that can result in cure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation